Answer:
Georgia would get 32 sweets and Courtney would get 56 sweets.
Step-by-step explanation:
This question asks you to find equivalent fractions or ratio. They give us the starting ratio of 4:7, which represents that for every four sweets that Georgia receives, Courtney receives 7. They also tell us that Courtney gets 24 more sweets than Georgia. If we let 'x' equal the number of sweets that Georgia receives and 'x+24' equal the number of sweets that Courtney receives, then we can set up a proportion where 4/7 = x/(x+24). We then can use cross-multiplication and division to solve for the value of 'x'. In this case 4(x +24) = 7x. We use distribution to get 4x + 96 = 7x, then inverse operations (subtracting 4x from both sides) to get 96 = 3x, then inverse operations to divide 3 by both sides to get x=32. 32 would be the number of sweets Georgia receives and 32+24=56 would be the number of sweets that Courtney receives.
Georgia and Courtney share sweets in the ratio 4:7, meaning for every 4 sweets Georgia gets, Courtney has 7. Given that Courtney gets 24 more sweets than Georgia, together they get a total of 88 sweets.
Explanation:This question is about the concept of ratio in mathematics. Georgia and Courtney share sweets in the ratio 4:7. This can also mean that for every 4 sweets Georgia gets, Courtney gets 7. But, the question mentions that Courtney gets 24 more sweets than Georgia.
Let's assume that Georgia gets 4x sweets and Courtney gets 7x sweets. So, 7x - 4x = 24, because Courtney gets 24 more sweets. Hence 3x equals to 24. Therefore, x = 24/3 = 8.
Now to find how many sweets each gets, we multiply their ratio parts by this value. For Georgia, we get: 4 * 8 = 32 sweets, and Courtney gets, 7 * 8 = 56 sweets. Both together get 32 + 56 = 88 sweets.
Learn more about Ratio here:https://brainly.com/question/32531170
#SPJ2
Help please in explain
Answer:
they are different numbers
Step-by-step explanation:
when you subtract 35-15 it comes out to 20 and the other one comes out to 17
Destiny reached the 3-km mark of the race at 10:36am and the 5-km mark at 10:44am. WHat is her running rate
Answer:
Running rate of Destiny is 15 kmph
Step-by-step explanation:
Running rate of Destiny is the speed at which Destiny is running.
It can be calculated by finding the difference in the distance covered to the difference in the time taken.
So,
Running rate = Difference in distance covered / Difference in time taken
Difference in distance covered = 5-3 = 2 km
Difference in time taken = 10:44 am - 10:36 am = 44 -36 minutes = 8 mins =8/60 hour = 2/15 hour
Running rate = 2/(2/15) kmph =(2*15)/2 = 15 kmph
∴Running rate of Destiny is 15 kmph
Find the length of segment AD.
Someone please help! I’m not the smartest when it comes to math lol.
Answer:
Since AG = GC then AD must equal DC
2x -3 = x +2
x = 5
Step-by-step explanation:
It takes 24 workers to complete the job in 5 days. How many days would 15 workers take to do the same job, assuming all the workers work at the same pace?
I'm guessing 10 days, since you lost a bit more than half of the workers, and it would take longer for the job to get done.
In isosceles trapezoid JKLM, m∠J = 17x + 7, and m∠M = 11x + 13. Find m∠K.
Final answer:
To find the measure of angle K in the isosceles trapezoid JKLM, set the expressions for angle J and angle M equal to each other and solve for x. Substituting the value of x into one of the angle expressions will give the measure of angle K.
Explanation:
To find the measure of angle K in the isosceles trapezoid JKLM, we can use the fact that the opposite angles in an isosceles trapezoid are congruent. Since angle J and angle M are given in terms of x, we can set them equal to each other and solve for x:
17x + 7 = 11x + 13
Simplifying the equation, we get:
6x = 6
x = 1
Now that we have the value of x, we can substitute it back into one of the angle expressions to find the measure of angle K:
m∠K = 17(1) + 7 = 24 degrees
In a geometric sequence, a2=108 and as 256. Write the explicit formula for this sequence.
Answer:
C. 81[-4/3]^n-1
Step-by-step explanation:
The explicit formula for a geometric sequence is given by a_n = a * r^(n-1). Using the provided values of a2 = 108 and a5 = 256, we can establish two equations to solve for 'a' and 'r'. This results in two possible explicit formulas for the sequence.
Explanation:In a geometric sequence, each term after the first is obtained by multiplying the previous term by a fixed, non-zero number called the common ratio. If we denote the first term of the sequence by 'a' and the common ratio by 'r', then the explicit formula of the sequence is: a_n = a * r^(n-1). Given that a2 = 108 (the second term is 108) and a5 = 256 (the fifth term is 256), we have two equations: a*r = 108 and a*r^4 = 256. Dividing the second equation by the square of the first equation, we get r^2 = 256/108^2 = 0.022. So, r is about +- 0.148. Substituting r into the first equation, we can solve for a. This gives us two possible explicit formulas for the sequence depending on whether we take the positive or negative value of r.
Learn more about Geometric Sequence here:https://brainly.com/question/33243139
#SPJ3
The manager of a store orders balance beams that cost $550 and sells them for $704. What percentage is the mark-up?
Answer:
28%
Step-by-step explanation:
Percentage mark up = (new - original) / original * 100 %
new = 704
original = 550
Substituting these values in
Percentage mark up = (704 - 550) / 550 * 100 %
=154/550 * 100%
=.28*100%
28%
A store sells 12 cans of nuts for $33. How much would it cost you to buy 5 cans of nuts?
[tex]\bf \begin{array}{ccll} cans&\$\\ \cline{1-2} 12&33\\ 5&x \end{array}\implies \cfrac{12}{5}=\cfrac{33}{x}\implies 12x=165 \\\\\\ x=\cfrac{165}{12}\implies x=13.75[/tex]
Answer:
$13.75
Step-by-step explanation:
Divide $33 by 12 to find out how much each can of nuts costs, which is $2.75. Now multiply that by 5 to get the cost of 5 cans of nuts. $13.75.
A website's views were increasing exponentially at a rate of 14% per year.
What was the monthly growth rate?
Enter your answer, rounded to the nearest tenth of a percent, in the box.
Answer:
see below PLEASE GIVE BRAINLIEST
Step-by-step explanation:
14% ÷ 12 (MONTHS IN THE YEAR) = 1.16666667
If rounding to the nearest 10th of a percent the answer is 1.2% increase per month.
Answer:
1.1%
Step-by-step explanation:
Annual rate: 14 % = [tex]\frac{14}{100} = 0.14[/tex]
Monthly rate = [tex](1 + r )^{\frac{1}{12} } - 1[/tex]
= [tex](1 + 0.14 )^{\frac{1}{12} } - 1[/tex]
= [tex](1.14 )^{\frac{1}{12} } - 1[/tex]
= 1.01097 - 1
= 0.01097
In percent it becomes: 0.01097 * 100 = 1.097%
Rounded to the nearest tenth: 1.1%
Rearrange the equation so b is the independent variable. 4a+b=−52
Answer:
[tex]a= \frac{-52-b}{4}[/tex]
Step-by-step explanation:
Rearrange the equation so b is the independent variable.
To get 'b' as a independent variable , we need to get 'a' alone
WE need to solve for 'a' so that 'a' depends on variable b and 'b' becomes independent variable
4a+b=−52
To get 'a' alone , subtract 'b' from both sides
4a = -52-b
Divide by 4 on both sides
[tex]a= \frac{-52-b}{4}[/tex]
Answer:
a=-13-1/4b
Step-by-step explanation:
I got it on khan academy I didn’t get what the guy before got but sorry if it’s wrong
what are the steps to multiplying a fraction by a fraction
Step-by-step explanation:
so for example lets say the fractions are 1/4 and 2/3
you would multiply them to make the eqution look like this- [tex]\frac{1}{4}[/tex]·[tex]\frac{2}{3}[/tex]
so then you would cross simplify, since 2 is a factor of 4 we will factor them out, so itll look like this=
[tex]\frac{1}{2}[/tex]·[tex]\frac{1}{3}[/tex]
then you multiply the denominator with denominato and numerator with numerator, so the answer is 1/6
Hello There!
To multiply fractions, you first want to line up the numerator and the denominator together so they line up with each other.
Next, you want to multiply across. This includes multiplying the numerators together and then multiplying the denominators together.
Finally, you want to find the greatest common factor but only if the fraction can be simplified.
That Is How To Multiply Fractions
Which expression is modeled by the diagram above?
PLEASE HELP ASAP!
Answer:
[tex]3\frac{1}{4}[/tex] divide by [tex]\frac{3}{4}[/tex]
Step-by-step explanation:
[tex]3\frac{1}{4}[/tex] is a mixed fraction and it can be written as
[tex]\frac{3*4+1}{4}=\frac{13}{4}[/tex]
13/4 can be break into
[tex]\frac{3}{4}+\frac{3}{4}+\frac{3}{4}+\frac{3}{4}+\frac{1}{4}[/tex]
[tex]\frac{13}{4}[/tex] can be divided into [tex]\frac{3}{4}[/tex] and it is left with
[tex]\frac{1}{4}[/tex]
[tex]3\frac{1}{4}[/tex] divide by [tex]\frac{3}{4}[/tex]
Which of the following is NOT a congruence transformation
A. A reflection over the x-axis
B. A dialation with scale factor 0.5
C. A translation 1 unit left
D. A dialation with scale factor 1
Plz I need by tonight
Answer: $9.75
Step-by-step explanation: I think this is how you do it. 20h=195 so you divide 195 by 20 to find our how much he gets an hour.
Answer:
9.75
Step-by-step explanation:
You have to divide the both by 20 since there is any like terms or anything to use, but you can use division on both sides since its 20h = 195.
20h = 195
-------------20 20
-------------h = 9.75
help?? #10 please!!
Answer:
∠CAT = 140°
Step-by-step explanation:
Since AB bisects ∠CAT then ∠BAT = ∠CAB, hence
5x + 20 = 2x + 50 ( subtract 2x from both sides )
3x + 20 = 50 ( subtract 20 from both sides )
3x = 30 ( divide both sides by 3 )
x = 10
∠CAT = ∠BAT + ∠CAB = 5x + 20 + 2x + 50 = 7x + 70
substitute x = 10 into the expression
∠CAT = (7 × 10) + 70 = 70 + 70 = 140°
Jackson deposited $5,000 at 3.8% interest, compounded continuously, when he was 18 years old. How much will be in the account when he is 40 years old if he made no other deposits or withdrawals?
With a principal of $5,000, an interest rate of 3.8%, over 22 years, Jackson's principal will grow to $11,535
Given: principal is $5000, interest rate is 3.8% and it is compounded continuously
To find: amount when Jackson is 40 years old
To solve this problem, we use the formula for continuous compounding interest:
[tex]A = P \times e^{rt}[/tex]
where:
A is the total amount of money
P is the principal
r is the annual interest rate (decimal form, so 3.8% becomes 0.038)
t is the time in years
Time here will be 22 years as Jackson deposited the money when he was 18 years old. So, the difference of 40 and 18 gives us 22 years.
Now we can find the total amount by plugging in the values:
[tex]A = 5000 \times e^{0.038 \times 22}\\[/tex]
[tex]A= 5000 \times e^{0.836}\\[/tex]
[tex]A= 5000 \times 2.307\\[/tex]
[tex]A = 11535[/tex]
Therefore, Jackson's account will have $11,535 when he is 40 years old.
Write the equation of the circle with center (3,-2), and passes through the point (0,2).
Final answer:
To find the equation of the circle, we need the center coordinates and the radius. In this case, the center is (3, -2) and the circle passes through the point (0, 2). Using the distance formula, the radius is found to be 5. Therefore, the equation of the circle is [tex](x - 3)^2 + (y + 2)^2 = 5^2[/tex].
Explanation:
To find the equation of a circle, we need the center coordinates and the radius. In this case, the center is (3, -2) and the circle passes through the point (0, 2). We can use the distance formula to find the radius, which is the distance between the center and the point on the circle.
Using the distance formula, [tex]d = \sqrt{((x2 - x1)^2 + (y2 - y1)^2)[/tex], we have:
[tex]d = \sqrt{((0 - 3)^2 + (2 - (-2))^2)} = \sqrt{((-3)^2 + (4)^2)} = \sqrt{(9 + 16)} = \sqrt{(25)} = 5[/tex]
So, the radius is 5. Therefore, the equation of the circle is
[tex](x - 3)^2 + (y + 2)^2 = 5^2[/tex]
To find the equation of the circle with center at (3, -2) and passing through the point (0, 2), use the standard form and calculate the radius. Then, the equation is (x - 3)² + (y + 2)² = 25.
To find the equation of a circle with center at (3, -2) and passing through the point (0, 2), we can use the standard form of the equation of a circle, which is:
(x - h)² + (y - k)² = r²
Here, (h, k) is the center of the circle, and r is the radius. Given the center (3, -2), we substitute h = 3 and k = -2:
(x - 3)² + (y + 2)² = r².
Next, we find the radius by calculating the distance between the center (3, -2) and the point (0, 2) using the distance formula:
r = [tex]\sqrt{(0 - 3)^2 + (2 + 2)^2}[/tex]
= √(9 + 16)
= √(25)
= 5.
With r = 5, we can now write the full equation of the circle:
(x - 3)² + (y + 2)² = 25
To summarize, the equation of the circle with center at (3, -2) and passing through the point (0, 2) is (x - 3)² + (y + 2)² = 25.
A and B are two events.
P(A) = 0.6, P(B) = 0.3, P(A and B) = 0.1.
What is the value of P(A or B)?
Answer:
0.8
Step-by-step explanation:
We can solve P(A or B) by using the following:
[tex]P(AorB)=P(A)+P(B)-P(AandB)[/tex]
Since we know P(A) = 0.6, P(B) = 0.3 and P(A and B) = 0.1 we obtain:
[tex]P(AorB)=0.6+0.3-0.1=0.8[/tex]
Answer: 0.8
Step-by-step explanation:
8 lb 1 oz − 3 lb 6 oz
Answer:
Since you want me to answer 3 lb 1 oz - 1 lb 15 oz instead, the answer is 18 oz
Step-by-step explanation:
First, convert pounds and ounces to just ounces, then subtract the total ounces. Finally, convert back to pounds and ounces to get the result of 8 lb 1 oz minus 3 lb 6 oz, which is 4 lb 11 oz.
Subtracting Mixed Measurements
To find the result of 8 lb 1 oz − 3 lb 6 oz, follow these steps:
Convert everything to ounces for easier subtraction (since there are 16 ounces in a pound).
Subtract the ounces first, then subtract the pounds.
Step-by-Step Solution
Step 1: Convert to ounces
8 lb 1 oz = (8 × 16) + 1 = 128 + 1 = 129 ounces
3 lb 6 oz = (3 × 16) + 6 = 48 + 6 = 54 ounces
Step 2: Subtract the ounces
129 ounces - 54 ounces = 75 ounces
Step 3: Convert back to pounds and ounces
75 ounces = 4 lb 11 oz (since 75 ÷ 16 = 4 remainder 11)
Therefore, 8 lb 1 oz − 3 lb 6 oz = 4 lb 11 oz.
solve the equation by completing the square. x^2 -6x -21=0 if the solution is not a real number enter no solution (ANSWER -2.48 and 8.48 )this is what the lesson says i just dont know how to show this
Answer:
see explanation
Step-by-step explanation:
given x² - 6x - 21 = 0 ( add 21 to both sides )
x² - 6x = 21
to complete the square
• add ( half the coefficient of the x-term)² to both sides
x² + 2 (- 3)x +9 = 21 + 9
(x - 3)² = 30 ( take the square root of both sides )
x - 3 = ± [tex]\sqrt{30}[/tex] ( add 3 to both sides )
x = 3 ± [tex]\sqrt{30}[/tex]
x = 3 - [tex]\sqrt{30}[/tex] = - 2.48 ( to 2 dec. places ) or
x = 3 + [tex]\sqrt{30}[/tex] = 8.48 ( to 2 dec. places )
Is this table linear or non linear?
x y
0 5
1 8
2 11
Answer:
Linear
Step-by-step explanation:
Each time x increases by one unit, y increases by three units.
The table represents a linear function of x.
What is the solution to the equation fraction 1 over 4x = 5?
A) x = fraction 4 over 5
B) x = fraction 5 over 4
C) x = 20
D) x = 1
Based on the graph, which inequality is correct for a number that is to the right of -3?
4 > −3
−3 > 4
−2 < −3
−3 < −6
Answer:
4 > −3
Step-by-step explanation:
To find a number to the right of -3, it must be bigger than -3
The open part of the inequality faces the bigger number.
4 is bigger than -3
4>-3
Please find the Sine, Cosine, and Tangent
Answer:
sin theta = 3/5
cos theta = 4/5
tan theta = 3/4
Step-by-step explanation:
sin = opposite / hypotenuse
cos = adjacent / hypotenuse
tan = opposite / adjacent
sin theta = 18/ 30 = 3/5
cos theta = 24/30 = 4/5
tan theta = 18/24 = 3/4
Answer:
[tex]sin \theta = \frac{3}{5} = 0.6\\\\ cos \theta = \frac{4}{5} = 0.8\\\\tan \theta = \frac{3}{4} = 0.75\\[/tex]
Step-by-step explanation:
Use SOHCAHTOA for reference
[tex]sin = \frac{opposite}{hypotenuse} \\\\cos = \frac{adjacent}{hypotenuse} \\\\tan = \frac{opposite}{adjacent}[/tex]
[tex]sin \theta = \frac{18}{30} = \frac{3}{5} = 0.6\\\\cos \theta = \frac{24}{30} = \frac{4}{5} = 0.8\\\\tan \theta = \frac{18}{24} = \frac{3}{4} = 0.75[/tex]
The steps below show the incomplete solution to find the value of q for the equation 4q - 2q - 4 = -1 + 21
Step 1: 4q - 2q - 4 = -1 + 21
Step 2: 4q - 2q - 4 = 20
Step 3: 2q - 4 = 20
Which of these is most likely the next step?
Answer:
As you did not provide any "next steps", I would do it this way:
2q - 4 = 20 // add 4 to both sides
2q = 24 // divide both sides by 2
q = 12
Answer:
2q-4=20
Step-by-step explanation:
Jennifer is making a cold cut platter using turkey and ham for an event that she is catering. She uses 90 slices of meat. If 63 of the slices of meat are turkey, what percent of the meat on the platter are ham? ALSO, PLEASE EXPLAIN. Thanks! :)
Answer:
30% of the meat on the platter is ham.
Step-by-step explanation:
90 slices = 100%
10% = 9 slices
90 - 63 = 27 slices (this is the amount of ham)
10% x 3 = 30% = 27 slices of ham
Answer:
27 slices of ham which is about 30% of the meat.
Step-by-step explanation:
In this problem we have given
no. of slices of meat=90
no of slices of turkey's meat=63
Percent of ham in platter=?
No of ham slices= Total slices -turkey slices
=90 - 63
= 27 slices
therefore no of ham slices=27
percent of ham slices=Ham slicesx100/total slices
=27x100/90%
=30%
Therefore percent of ham's in patter=30%
Enter the correct answer in the box.
Solve the inequality for x in terms of a.[tex]ax-8\leq 12[/tex]
Answer:x<=(20)/(a)
Step-by-step explanation:
Simplify the algebraic expression: 7x2 + 6x – 9x – 6x2 + 15.
A. x2 – 3x + 15
B. x4 – 3x + 15
C. x2 + 15x + 15
D. 13x2 + 3x + 15
Answer:
The correct answer option is A. x2 – 3x + 15.
Step-by-step explanation:
We are given the following expression and we are supposed to simplify it:
[tex]7x^2+6x-9x-6x^2+15[/tex]
Before solving it, a good idea will be to arrange all the like terms together in their decreasing power and write the expression as:
[tex]7x^2-6x^2+6x-9x+15[/tex]
Simplifying it to get:
[tex]x^2-3x+15[/tex]
Therefore, the first option A is the correct answer x2 – 3x + 15.
Answer:
A. [tex]x^{2} - 3x +15[/tex]
Step-by-step explanation:
Given:
7x^2 + 6x – 9x – 6x^2 + 15.
On combining the x^2, and "x" terms we get,
= (7x^2 – 6x^2) + (6x – 9x) + 15
Now, here simple addition of integers takes places
= x^ - 3x + 15
What are the zeros of the quadratic function f(x)=2x^2+16x-9
Answer:
D
Step-by-step explanation:
The quadratic formula is
[tex]x=\frac{-b+\sqrt{b^2-4ac} }{2a}[/tex].
It is important because while some quadratics are factorable and can be solved not all are. The formula will solve all quadratic equations and can also give both real and imaginary solutions. Using the formula will require less work than finding the factors if factorable. We will substitute a=2, b=16 and c=-9.
[tex]x=\frac{-b+/-\sqrt{b^2-4ac} }{2a}\\x=\frac{-(16)+/-\sqrt{(16)^2-4(2)(-9)} }{2(2)}\\x=\frac{-16+/-\sqrt{256+72} }{4}[/tex]
We will now simplify and solve.
[tex]x=\frac{-16+/-\sqrt{328}}{4}\\x=-4+/-\sqrt{\frac{328}{16}}\\x=-4+/-\sqrt{\frac{41*8}{2*8}}\\x=-4+/-\sqrt{\frac{41}{2}}[/tex]
Can 12 be part of more than one fact family? Explain.